Low-dose perampanel improves refractory cortical myoclonus by the dispersed and suppressed paroxysmal depolarization shifts in the sensorimotor cortex. Issue 10 (October 2019) - Oi, Kazuki; Neshige, Shuichiro; Hitomi, Takefumi; Kobayashi, Katsuya; Tojima, Maya; Matsuhashi, Masao; Shimotake, Akihiro; Fujii, Daiki; Matsumoto, Riki; Kasama, Shuhei; Kanda, Masutaro; Wada, Yoshiaki; et al.
Highlights: Low dose of perampanel (PER) is tolerable and effective to ameliorate refractory cortical myoclonus. PER suppresses and disperses paroxysmal depolarization shifts directly on the postsynaptic neurons. This action was reflected by temporal dispersion in giant SEPs (a potential clinical biomarker). Abstract: Objective: To elucidate the effects of perampanel (PER) on refractory cortical myoclonus for dose, etiology and somatosensory-evoked potential (SEP) findings. Methods: We examined 18 epilepsy patients with seizure and cortical myoclonus. Based on data accumulated before and after PER treatment, correlations among clinical scores in myoclonus and activities of daily life (ADL); early cortical components of SEP; and PER blood concentration, were analyzed. Results: PER (mean dose: 3.2 ± 2.1 mg/day) significantly improved seizures, myoclonus and ADL and significantly decreased the amplitude of and prolonged latency of giant SEP components. The degree of P25 and N33 prolongations (23.8 ± 1.6 to 24.7 ± 1.7 ms and 32.1 ± 4.0 to 33.7 ± 3.4 ms) were significantly correlated with improved ADL score (p = 0.019 and p = 0.025) and blood PER concentration (p = 0.011 and p = 0.025), respectively. Conclusions: Low-dose PER markedly improved myoclonus and ADL in patients with refractory cortical myoclonus. Our results suggest that SEP, particularly P25 latency, can be used as a potential biomarker for assessing the objective effects of PER on intractable cortical myoclonus. Significance: In this study, PER lessened the degree of synchronized discharges in the postsynaptic neurons in the primary motor cortex.